Effect of Neurodevelopmental Treatment Frequency on Functional Abilities in Children with Cerebral Palsy: A Literature Review - Liviyanti, Dinia; Pratama, Aditya Denny (Majalah Ilmiah Fisioterapi Indonesia; Vol 13 No 2 (2025): Majalah Ilmiah Fisioterapi Indonesia, 2025)
Introduction: Cerebral palsy (CP) is a major cause of motor dysfunction in children, often requiring comprehensive and long-term rehabilitation. Neurodevelopmental Treatment (NDT) is a commonly applied intervention designed to improve motor control, posture, and functional abilities. This review aims to examine how the frequency of NDT therapy affects functional outcomes in children with CP. Methods: A systematic literature review was conducted using PubMed, ProQuest, Scopus, and Google Scholar. Six peer-reviewed articles published between 2013 and 2023 were selected based on inclusion criteria: studies involving children with CP who received NDT therapy and assessed outcomes such as gross motor function, balance, postural control, or occupational performance. Keywords used included "Neurodevelopmental Treatment," "cerebral palsy," "therapy frequency," and "functional ability." Results: The findings indicate that a higher frequency of NDT therapy (three to five sessions per week) is associated with more significant improvements in gross motor skills, postural control, and balance. However, lower-frequency therapy (twice weekly) also produced positive outcomes when delivered consistently. Four of the six studies showed greater benefits with high-frequency sessions, while the remaining two reported notable improvements at lower frequencies. Moreover, combining NDT with complementary approaches such as the CO-OP method or Bobath therapy enhanced functional performance and parent-reported satisfaction. Conclusion: Therapy frequency plays a crucial role in determining the functional outcomes of children with CP undergoing NDT. While high-frequency therapy offers optimal benefits, consistent low-frequency sessions can still be effective. Clinicians should individualize therapy plans based on each child's needs to achieve the best possible rehabilitation outcomes. Keywords: cerebral palsy, Neurodevelopmental Treatment, functional ability, therapy frequency, rehabilitation